2019
DOI: 10.1177/0001839219869913
|View full text |Cite
|
Sign up to set email alerts
|

Election Cycles and Organizations: How Politics Shapes the Performance of State-owned Enterprises over Time

Abstract: This study develops a dynamic perspective on how elected state officials’ political incentives shape the behavior and performance of organizations, particularly state-owned enterprises (SOEs). Drawing on theoretical views about the relationship between politicians and firms, I argue that state officials seeking votes manipulate SOEs to boost employment before elections. As a result, SOEs exhibit both higher employment levels and lower financial performance in election years. The positive relationship between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 111 publications
(188 reference statements)
0
21
0
Order By: Relevance
“…Recent works show that firms can time investment decisions along the political cycle to pursue political objectives. For instance, stateowned firms have been shown to increase investment and employment during election times as a means to construct voter support (Alok & Ayyagari, 2020;Inoue, 2020). Going beyond state-owned firms, there is evidence that firms with social ties with politics increase employment during an election to support incumbent politicians (Bertrand et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent works show that firms can time investment decisions along the political cycle to pursue political objectives. For instance, stateowned firms have been shown to increase investment and employment during election times as a means to construct voter support (Alok & Ayyagari, 2020;Inoue, 2020). Going beyond state-owned firms, there is evidence that firms with social ties with politics increase employment during an election to support incumbent politicians (Bertrand et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Political changes characterized by regular elections are highly significant elements of the political landscape in many countries. It has been shown that elections influence organizational outcomes in settings marked with politically embedded organizations linked to state actors (Inoue, 2019), and it is indeed important for managers to deal with the political environment to enhance their firms' market performance. Moreover, studies have concluded that decoupling market and political environments may be problematic in some contexts in which they are closely interrelated (Guo et al, 2017;Oliver & Holzinger, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This study furthers the nascent research on political ideology by proposing a dynamic political perspective on firmlevel outcomes by looking at humor magazines. In so doing, we have sought to develop the incomplete view of how firm behavior is impacted by political dynamics during political cycles (Inoue, 2019). While our work is revelatory, it is focused on achieving a deep understanding of the dynamics at play in a given context (Eisenhardt, 1989) and is therefore particularly suited to examining phenomena that have received limited scholarly attention, such as, in our case, the influence of political context on ideological imprinting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations